NATURAL GENESIS FOUNDATION AVAR ORNAMENTAL ART - G. G. Gazimagomedov (Юг России: экология, развитие)
The work deals with Avarian ornamental art - it is the only phenomena in decoration applied art. Special attention is paid to succession of the traditions important for conservation and further development of the natural art trade of Daghestan republic.